Gambaran Penggunaan Obat Kardiovaskular, Faktor Usia Dan Jenis Kelamin Pasien Gagal Jantung Yang Dirawat Di Rsup Dr. M. Djamil Padang (Periode Oktober-Desember Tahun 2023 - Elsa Marsellinda; Dea Suci Aulia (STIKes Ibnu Sina Ajibarang, 2024)
Heart failure is a complex clinical syndrome due to functional or structural ventricular dysfunction. The goal of treating heart failure is to reduce morbidity and mortality and prevent the worsening of heart disease. The purpose of this study was to describe the pattern of heart failure drug therapy at Dr. M Djamil Hospital Padang. Data were collected retrospectively from the medical records of heart failure patients admitted to the cardiac ward. period October to December 2023 analyzed descriptively. Results: In this study, based on gender, 59 (56.19%) female patients and 46 (43.81%) men. Based on age, the most patients (29.52%) were in the early elderly group (56-65 years), followed by 28.57% in the 46-55 years group, and 20% in patients aged 65 years and over. The youngest age in this study was 18 years and the oldest age was 87 years. Based on cardiovascular drug therapy, furosemide (31.29%) followed by ramipril (21.09%) and candesartan (15.65%). Conclusion: based on the results of the study it can be concluded that female patients are more than men, based on the age of the early elderly age group more, and the most widely used therapy is furosemide, followed by ACEI, and ARB.